The response of honeycomb sandwich panels to blast loads - Chi, Yunn-Chih (Yvonne) (Department of Mechanical Engineering, 2014)
Numerous studies have been performed in search of structures providing better blast protection and to understand the various effects influencing the structural performance. This thesis reports on an investigation into the behaviour of circular sandwich panels with aluminium honeycomb cores subjected to air blast loading. It focuses on the effect of varying core thickness, plate thickness and panel configuration. In this study, aluminium honeycomb core is sandwiched between mild steel face plates. Quasi-static tensile and compression experiments are performed to characterise the face plates and the honeycombs. Four sandwich panel configurations are proposed and subjected to blast loading. The impulse is generated by detonating plastic explosives at a constant stand-off distance and measured using a ballistic pendulum. The impulse is varied by using different charge masses. It is observed that the panels experience front plate deflection and tearing; honeycomb core crushing and densification; and back plate deflection and tearing. The deformations of the face plates and the cores increased with increasing impulse. Increasing the core thickness delayed the onset of core densification and decreased back plate deflection; and increasing the plate thickness also decreased back plate deflection. The use of an extra sandwich layer helps to provide better structural support but has the penalty of extra mass.